2020
DOI: 10.1002/cctc.201902112
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Grinding synthesis of La(Sr,Ce)CoO3 and their properties in toluene catalytic total oxidation

Abstract: Perovskites-type metal oxides are an attractive alternative to noble metal-based materials for environmental catalysis. Nevertheless, they suffer from major issues such as unattractive textural properties and lower intrinsic activities than those of noble metal counterparts. Reactive grinding (RG) has been already proved to be a powerful method to produce materials with improved textural properties. La 1-x A' x CoO 3 (A': Sr, Ce) perovskite-type materials were synthesized by RG synthesis as a 3-steps top down … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…As shown in Figure b, the E a values for VOC oxidation followed the order of LaCoO 3 < SmCoO 3 < GdCoO 3 , suggesting that LaCoO 3 had the highest concentration of surface-active species, which led to the greater susceptibility of VOC to oxidation over LaCoO 3 . Furthermore, the E a values over LaCoO 3 (52.4 kJ·mol –1 ), SmCoO 3 (60.1 kJ·mol –1 ), and GdCoO 3 (66.7 kJ·mol –1 ) were also significantly lower than those of LaMnO 3 (84.0 kJ·mol –1 ), LaCoO 3 (173.0 kJ·mol –1 ), Eu 0.6 Sr 0.4 FeO 3 (78.8.0 kJ·mol –1 ), and La 0.6 Sr 0.4 Fe 0.8 Bi 0.2 O 3‑δ (127.7 kJ·mol –1 ), Cu 1.5 Mn 1.5 O 4 (111.2 kJ·mol –1 ), MnO/CeO 2 (>127.6 kJ·mol –1 ), MnO x /Al 2 O 3 (133.0 kJ·mol –1 ), and Ni 0.5 Zn 0.5 Fe 2 O 4 (94 kJ·mol –1 ) . In general, the activity of catalysts is determined by their structures, metal states, and redox properties, which can be improved through optimized preparation methods. , Therefore, we attribute the difference in E a values between RECoO 3 and the literature values to the high concentration of surface-active species in RECoO 3 , obtained through direct calcination of the viscous mixture.…”
Section: Resultsmentioning
confidence: 85%
“…As shown in Figure b, the E a values for VOC oxidation followed the order of LaCoO 3 < SmCoO 3 < GdCoO 3 , suggesting that LaCoO 3 had the highest concentration of surface-active species, which led to the greater susceptibility of VOC to oxidation over LaCoO 3 . Furthermore, the E a values over LaCoO 3 (52.4 kJ·mol –1 ), SmCoO 3 (60.1 kJ·mol –1 ), and GdCoO 3 (66.7 kJ·mol –1 ) were also significantly lower than those of LaMnO 3 (84.0 kJ·mol –1 ), LaCoO 3 (173.0 kJ·mol –1 ), Eu 0.6 Sr 0.4 FeO 3 (78.8.0 kJ·mol –1 ), and La 0.6 Sr 0.4 Fe 0.8 Bi 0.2 O 3‑δ (127.7 kJ·mol –1 ), Cu 1.5 Mn 1.5 O 4 (111.2 kJ·mol –1 ), MnO/CeO 2 (>127.6 kJ·mol –1 ), MnO x /Al 2 O 3 (133.0 kJ·mol –1 ), and Ni 0.5 Zn 0.5 Fe 2 O 4 (94 kJ·mol –1 ) . In general, the activity of catalysts is determined by their structures, metal states, and redox properties, which can be improved through optimized preparation methods. , Therefore, we attribute the difference in E a values between RECoO 3 and the literature values to the high concentration of surface-active species in RECoO 3 , obtained through direct calcination of the viscous mixture.…”
Section: Resultsmentioning
confidence: 85%
“…are regarded as inert in catalysis and act as a rigid structural element in the crystal of perovskite oxides, while the B-site transition metal elements (e.g., Co, Mn, Fe, etc.) are mainly responsible for catalytic activity. , However, it should be noticed that the valence states of B-site redox elements and the crystal structure in perovskite oxides can be effectively altered by doping with both of A/B-site elements, which will also trigger the formation of abundant oxygen vacancies and lead to enhancement of oxygen mobility. In previous studies, the low-valence elements (such as K, Sr, Ca, Co, Ni, and Cu) were usually applied to dope into the A/B-sites of various perovskite oxides to further improve their catalytic activity. For example, Zhao et al reported the effect of different doping contents of Co 2+ in the B-site of LaFeO 3 on chemical looping steam methane reforming. They found that the substitution of Fe with an appropriate content of Co could promote the generation of oxygen vacancies, improve the reducibility of LaFe 1– x Co x O 3 , and change the types of oxygen species, which eventually facilitated the partial oxidation of methane, inhibited the direct decomposition of methane, and produced more hydrogen in chemical looping methane reforming.…”
Section: Introductionmentioning
confidence: 99%
“…Catalytic oxidation is regarded as one of the promising approaches to control the emission of VOCs due to its high efficiency. [8][9][10] The catalysts for VOCs removal are usually included supported noble metals (i. e. Pt, Pd and Rh) and transition metal oxides (Mn, Cu, Co, Cr and Ce). Compared with noble metal catalysts, transition-metal oxides are attractive due to their low cost, high thermal stability and promising activity.…”
Section: Introductionmentioning
confidence: 99%